Toxicopathological study of aqueous extract of beetle cocoon Larinus maculatus F. on some internal organs in male albino mice - Tawfiq, Iqbal Naji (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was carried out to investigate the effect of oral administration of hot aqueous extract of beetle cocoon Larinus maculatus Faldermann, in a two doses 50and100mg/Kg/Bw for 25 and 45days respect- tively on some organs such as liver, lung, kidney, intestine, heart, spleen, and brain in male mice Mus musculus. The results indicated that there were toxicopathological changes in many tissues of experimental animals. Histo -pathological changes was dose and period dependent . It was found that the aqueous extract of beetle cocoon has undesirable effect at the administered doses, since the raw extract of this cocoon is currently being used in Folk medicine as treatment for cough, bronchitis in Iraq. This study revealed that the low doses of this extract have some deleterious effects on certain organs, so it should not be used for long durations in control of respiratory disease.